2012
DOI: 10.1111/j.1365-2702.2012.04253.x
|View full text |Cite
|
Sign up to set email alerts
|

Pain management and satisfaction in postsurgical patients

Abstract: Acute postoperative pain is an ongoing issue for postsurgical patients. It is crucial to understand and recognise issues that can adversely contribute to increased pain severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 52 publications
4
17
0
5
Order By: Relevance
“…2 In the United Kingdom a study performed in 2012 revealed that 68% of postoperative patients experienced pain, of which 38% reported severe pain and 52% moderate pain. 4 The incidence of acute postoperative pain in our single-centre developing country referral hospital was high in comparison with developed countries even though patients from lower income groups have a tendency to underreport their pain. 15 In 62% of patients, moderate or severe pain occurred at least once during the first postoperative day.…”
Section: Incidence Of Painmentioning
confidence: 99%
See 3 more Smart Citations
“…2 In the United Kingdom a study performed in 2012 revealed that 68% of postoperative patients experienced pain, of which 38% reported severe pain and 52% moderate pain. 4 The incidence of acute postoperative pain in our single-centre developing country referral hospital was high in comparison with developed countries even though patients from lower income groups have a tendency to underreport their pain. 15 In 62% of patients, moderate or severe pain occurred at least once during the first postoperative day.…”
Section: Incidence Of Painmentioning
confidence: 99%
“…Patients who received emergency surgery had a much higher incidence of inadequate analgesia when compared with their elective counterparts in our and a previous study. 4 During emergency surgery the lack of premedication, inadequate preparation and other seemingly more important clinical challenges may take the focus away from measuring pain and administering analgesia. Preoperative pain has also been shown to be a predictor of worse postoperative pain.…”
Section: Comparison Of Patient Populations To Identify Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Accurately measuring the effectiveness of acute pain management post major surgery is intertwined with measuring overall patient satisfaction. Traditional patient satisfaction surveys depend on patient recall of their inpatient care after discharge (Tocher et al 2012). A critical element of quality evaluation is obtaining direct feedback from patients about the here-and-now pain experiences in the immediate phase post surgery.…”
Section: Study Backgroundmentioning
confidence: 99%